Porous structure design of carbon xerogels for advanced supercapacitor. (1st September 2015) - Liu, Xichuan; Li, Shaomin; Mi, Rui; Mei, Jun; Liu, Li-Min; Cao, Liujun; Lau, Woon-Ming; Liu, Hao
Highlights: Adopting M–R–F gels for nitrogen-doping and micron-duct formation. Incorporation of PEO–PPO–PEO micelles for the micron-channels optimization. Integration of CO2 activation process for the formation of abundant micropores. Nitrogen-doped carbon with hierarchical porous structure has been achieved. High performance for supercapacitor has been realized. Abstract: A porous carbon electrode incorporating considerations both heteroatom doping and pore structure design with: combination of melamine and PEO–PPO–PEO (polyethylene oxide–polypropylene oxide–polyethylene oxide) micelles for the nitrogen-doping and optimization the micron-duct formation; integration of CO2 -etching into the carbonization process for the formation of abundant micropores. The structure of these nitrogen-doped carbon xerogels (NCXs) are indeed comprised of a multi-scaled pores having nano-porous carbon in a network of micron-size percolated hollow-channels. The resulted material has an ultrahigh surface area of 4279 m 2  g −1 when used as electrode for supercapacitor, which deliver a high specific capacitance of 271 F g −1 with excellent cycle stability and good rate capability.